Method for testing residual stress of laying process SiCf / SiC composite material matrix

By preparing specific laying structures and introducing pre-cracks in SiCf/SiC composites, the problem that the prior art cannot effectively detect the residual stress of the matrix of SiCf/SiC composites is solved, and accurate measurement of the residual stress of the matrix and acquisition of multi-parameter mechanical data is achieved.

CN119510130APending Publication Date: 2025-02-25AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411583095.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing residual stress detection methods cannot effectively test the residual stress of the inner matrix of SiCf/SiC composite materials in the laying process, and conventional methods are greatly affected by material heterogeneity, making it difficult to reflect the residual stress state of the overall material.

Method used

A SiCf/SiC composite plate with a laying layer of [(90°)3/(0°)6/(90°)3] was prepared by prepreg-permeable process. By cutting straight strip samples and introducing pre-cracks into the samples, a double cantilever beam sample was formed, and the residual stress of the matrix was measured by bending deformation.

Benefits of technology

This method can accurately measure the residual stress of the SiCf/SiC composite matrix without destroying the material, overcome the disadvantages of the existing method being affected by material heterogeneity, and obtain multiple mechanical parameters in one test.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119510130A_ABST
    Figure CN119510130A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of composite material residual stress detection, and particularly relates to a method for testing residual stress of a laying process SiCf / SiC composite material matrix, which comprises the following steps of: preparing a SiCf / SiC composite material flat plate with a laying layer of [(90-degree) 3 / (0-degree) 6 / (90-degree) 3] by adopting a prepreg-infiltration process, and then cutting a straight strip sample on the flat plate; the method comprises the following steps: designing samples with a specific layering sequence by utilizing a distribution rule of residual stress in 0-degree layering and 90-degree layering of a layering composite material, and acquiring a laminate material modulus EX, a material modulus E0 in a 0-degree direction and a material modulus E90 in a 90-degree direction by utilizing different samples; and finally, calculating the residual compressive stress of the matrix by utilizing a residual stress theoretical formula based on a beam theory. According to the test scheme designed by the invention, the relationship between the residual stress and the bending curvature is established based on the beam theory of the composite laminate, and a plurality of modulus parameters of the material and the interlayer fracture toughness of the material can be obtained in the test process of the residual stress.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of residual stress detection of composite materials, and specifically relates to a lamination process SiC f Testing method for residual stress of matrix of SiC composite materials. Background Art

[0002] Commonly used SiC f The densification processes of / SiC composite materials mainly include chemical vapor infiltration (CVI), polymer precursor impregnation and cracking (PIP) and melt infiltration (MI). Among them, the material that uses unidirectional prepreg plying and then melt-infiltrating silicon to achieve matrix densification is popular because of its short preparation cycle and can achieve SiC f / SiC composite materials are produced stably in batches with excellent performance.

[0003] Residual stress detection is of great significance for the design, manufacture and application of materials. First of all, understanding the residual stress distribution helps to optimize the microstructure and macroscopic properties of the material. By adjusting the process parameters, the adverse residual stress can be reduced, thereby improving the strength of the material. In addition, understanding the residual stress can help prevent and reduce the occurrence of cracks and extend the service life of the material. In structural design, by measuring the residual stress value, the test results of components and simulations can be better analyzed, and it is expected to obtain a more optimized structural design based on the residual stress.

[0004] There are many existing residual stress detection methods. Depending on whether the tested component is damaged during the test process, they can be divided into mechanical detection methods and non-destructive detection methods. The principle of the mechanical measurement method is to separate or cut the components with residual stress from the components to release the stress, thereby generating corresponding strain and displacement, and to establish the stress-strain relationship according to the corresponding mechanical principles to calculate the residual stress. Common mechanical measurement methods: drilling method, ring core method, blind hole method, stripping method, stripping method, etc. The principle of the non-destructive measurement method is to use the characteristics of sound, light, magnetism and electricity to measure residual stress without damaging or affecting the performance of the measured object. Common non-destructive measurement methods: magnetic measurement method, X-ray diffraction method, ultrasonic method, indentation strain method, etc. The above-mentioned residual stress test methods are mostly proposed for isotropic and uniform metal materials, and they are not used in the prepreg-MI process SiC of the laminate structure. f It is not applicable to residual stress testing of SiC composite materials.

[0005] In order to measure the prepreg-MI process SiC of the laminate structure f To understand the residual stress in SiC composite materials, we need to first understand the mechanism and distribution characteristics of residual stress. fThe preparation process of SiC / SiC composite materials involves multiple high-temperature heat treatment steps. Due to the differences in stiffness and thermal physical properties of SiC fibers, SiC matrix, and interface layer, when the high temperature of preparation is lowered to room temperature, the above components will inevitably have residual stress. The residual stress will affect the bonding strength between the matrix and the interface layer, and ultimately affect the SiC f / SiC composites have a significant impact on the strength, toughness, thermal expansion and other properties on a macro scale. Compared with SiC fibers, there will be a certain compressive residual stress in the SiC matrix. This residual stress puts the SiC matrix in a slightly compressed state, which is beneficial for avoiding micro cracks in the SiC matrix. SiC fibers will be subject to a residual tensile stress to a certain extent, which also takes advantage of the excellent tensile properties of the fibers.

[0006] Existing mechanical measurement methods such as drilling method, ring core method, blind hole method, stripping method, and stripping method can only measure the residual stress at a local specified position of the material. It is difficult to apply them to inhomogeneous SiC f / SiC composites are easily affected by the uneven microstructure of the material and cannot reflect the f / SiC composite material as a whole residual stress state. In addition, the above method can generally only measure the residual stress on the surface of the material. Although the delamination method can measure internal and macroscopic residual stress, it requires mechanical grinding of the sample, which will inevitably introduce new residual stress and destroy the initial stress state inside the material. Non-destructive non-destructive measurement methods are based on physical optics or nuclear physics technology to measure the changes in physical constants (such as lattice constants) inside the material, and indirectly calculate the residual stress inside the material. However, the data obtained by this method needs to undergo complex processing and analysis, and requires in-depth research and exploration for specific materials. It is not a universal technology. In addition, the testing cost of the non-contact method is high, and it requires the purchase of professional instruments. It has high requirements on the professional skills of the operator and is not suitable for engineering applications.

[0007] In general, the prepreg-MI process prepared SiC laminate f The residual stress distribution law of SiC / SiC composites is different from that of other materials, and even ceramic-based composites prepared by different processes. There is no matrix residual stress detection method specifically suitable for this material, and the existing residual stress test methods cannot solve the problem of testing the matrix residual stress inside the laminate. Summary of the invention

[0008] The purpose of the present invention is to provide a layering process SiC f / SiC composite material matrix residual stress test method, in order to solve the existing residual stress test method can not test the layer process SiC f Technical issues on residual stress of matrix inside SiC composites.

[0009] To solve this technical problem, the technical solution of the present invention is:

[0010] A layering process SiC f A method for testing residual stress of a SiC composite material matrix, the method comprising the following steps:

[0011] Step 1: Prepare a SiCf / SiC composite material plate with a layer of [(90°)3 / (0°)6 / (90°)3] by using a prepreg-melt infiltration process, and then f At least three straight specimens are cut from the middle of the / SiC composite material plate; when used for comparative tests, the number of specimens cut is a multiple of 3.

[0012] Step 2: Cut a groove at one end of the first straight strip sample at the mid-surface along the thickness direction. The height of the groove is no more than 1 / 10 of the thickness of the sample, and the depth of the groove is 5 to 10 times the thickness of the sample.

[0013] Step 3: vertically place the first straight strip sample in a fixture that clamps the sample along the thickness direction, "wedge" a thin blade into the groove, and introduce a pre-crack into the middle surface (the middle position) of the first straight strip sample in the thickness direction to obtain a double cantilever beam (DCB) sample;

[0014] Step 4: Paste loading blocks on the upper and lower surfaces of the slotted side of the DCB specimen, and use the loading method of the double cantilever beam test to pull the DCB specimen apart from the prefabricated crack on the middle surface. The upper and lower arms of the separated DCB specimen are both asymmetric [(90°)3 / (0°)3] plies. Due to the release of residual stress, the upper and lower arms will bend toward the surface where the 90° ply is located, turning into a bent specimen.

[0015] Step 5: Measure the contours of the two bending specimens, and select several points in the middle of the outer contour arc to determine the curvature radius ρ of the bending specimens, then measure the thickness t and width W of the bending specimens and take the average value;

[0016] Step 6: Load the second straight strip sample in the range of -70MPa to +70MPa, measure the strain during loading, draw a stress-strain curve, and use the slope of the curve as the modulus E of the [(90°)3 / (0°)6 / (90°)3] ply sample. X ;

[0017] According to SiC f / SiC composite material characteristics, the sample loading strength is set to -70MPa ~ +70MPa range, within this range, to ensure that SiC fThe tensile stress on the SiC composite material is below the proportional limit, ensuring that the material exhibits a linear elastic stress-strain relationship. At this time, the slope of the stress-strain is the modulus of the specimen.

[0018] Step 7: Grind the upper and lower surfaces of the third straight strip sample, cut off the 90° ply close to the epidermis, obtain a straight strip sample with a ply of [0°]6, and then polish the two surfaces of the sample with diamond paste;

[0019] Step 8: Load the straight strip specimen of [0°]6 ply in the range of -70MPa to +70MPa, measure the strain during loading, draw the stress-strain curve, and use the slope of the curve as the SiC f / The modulus E0 of SiC composite material at 0° direction;

[0020] Step 9: Use the measured compression modulus E of the [(90°)3 / (0°)6 / (90°)3] ply sample X 、SiC f / SiC composite material 0° direction tensile modulus E0, reverse calculation of SiC f Modulus E of SiC composite material at 90° direction 90 ;

[0021] Step 10: The curvature radius ρ, sample thickness t, sample width W, modulus E0, modulus E 90 Substitute into the theoretical formula (1) to calculate the residual compressive stress σ of the matrix R ;

[0022]

[0023] Among them, σ R For SiC f / SiC composite matrix residual compressive stress; E0 is SiC f The modulus E0 of the SiC composite material at 0° direction; I0 is the modulus of SiC with a ply ratio of [(90°)3 / (0°)3] f / SiC composite material bending specimen moment of inertia; ρ is the curvature radius of the bending specimen; t is the thickness of the bending specimen;

[0024] Among them, the expression of the moment of inertia I0 is shown in formula (2):

[0025]

[0026] Where W is the width of the bending specimen; α and β are intermediate variables, and the expressions are shown in formula (3) to formula (4):

[0027]

[0028] SiC prepared in step 1 f The size of the SiC composite plate should be large enough, and the recommended size is 120 mm long × 120 mm wide. f The three straight specimens cut from the middle of the SiC composite material plate should be in the shape of thin strips, with the recommended size of 100 mm long × 10 mm wide.

[0029] When the vertically placed straight strip specimen is clamped in the fixture in step 3, it is recommended that the length of the clamping edge from the root of the groove is about 10 mm, and the clamping force needs to be large enough to prevent the specimen from sliding.

[0030] Preferably, the operation of "wedging" a thin blade into the groove to preform a mid-surface crack in step three is in accordance with ASTM C1940-24.

[0031] Step 9 Calculate SiC based on the modulus mixing law f Modulus E of SiC composite material at 90° direction 90 The theoretical formula of is shown in formula (5),

[0032] E 90 =2E X -E0(5)

[0033] Among them, E 90 For SiC f Modulus E of SiC composite material at 90° direction 90 ; E X The modulus of the straight specimen of the [(90°)3 / (0°)6 / (90°)3] ply.

[0034] This method is applicable to SiC laminated structures prepared by prepreg melt infiltration (MI) process. f / SiC composite materials.

[0035] The SiC layering process f / SiC composite materials are prepared using unidirectional prepreg.

[0036] Preferably, the height of the groove in step 2 is no more than 0.5 mm, and the depth of the groove is 10 mm.

[0037] Preferably, the groove in step 2 is cut by water-conducting laser.

[0038] Preferably, in step five, an imager is used to map the contours of the two bending specimens; and a vernier caliper is used to measure the thickness and width of the bending specimens.

[0039] Preferably, the strain in step six and step eight is measured using an extensometer.

[0040] Preferably, the samples in step six and step eight are both loaded using a mechanical testing machine.

[0041] In step seven, diamond paste with finer particle size, preferably 1 μm, is used to reduce the surface stress introduced by mechanical grinding.

[0042] The beneficial effects of the present invention are:

[0043] The present invention is based on the layering process SiC f / SiC composite materials have the characteristics of residual compressive stress in 0° plies and residual tensile stress in 90° plies. Therefore, when the straight strip specimen is cut from a symmetrical ply to an asymmetrical ply, bending deformation will occur under the action of residual stress. The specimen with a specific ply sequence is designed, so that the prepared symmetrical ply specimen is cut from the middle and becomes an asymmetrical ply, and the moment balance is broken, and bending deformation occurs under the action of residual stress. The test plan is designed, and the relationship between residual stress and bending curvature is established based on the beam theory of composite laminates. The residual tensile stress in the 0° ply is calculated. According to the balance of force, the residual tensile stress in the 0° ply is equal to the residual compressive stress in the 90° ply, which is the residual compressive stress of the matrix. During the test of the present invention, the loading method of measuring interlaminar fracture toughness by double cantilever beam is used to cut the symmetrical ply specimen from the middle, and the type I interlaminar fracture toughness of the material can be measured at the same time. By testing the modulus of the 0° ply specimen and the modulus of the orthogonal ply specimen, the modulus of the material in the 0° and 90° directions is obtained, and multiple mechanical parameters can be obtained in one test. The specific advantages are:

[0044] (1) Multiple material modulus parameters and interlaminar fracture toughness can be obtained during the residual stress test, achieving multiple goals at one stroke.

[0045] (2) It overcomes the disadvantage that the existing measurement methods are greatly affected by the material's own heterogeneity in the measurement of residual stress of composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to more clearly illustrate the technical solutions implemented in the present invention, the following is a brief explanation of the drawings required to be used in the examples of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0047] Figure 1 It is the implementation flow chart of the present invention

[0048] Figure 2 It is a layered SiC f Schematic diagram of the ply laying sequence of / SiC composite materials;

[0049] Figure 3It is a layered SiC f Schematic diagram of cutting three straight strips of samples in the middle of / SiC composite materials;

[0050] Figure 4 It is a three-dimensional schematic diagram of the groove cut at one end of the first straight bar specimen;

[0051] Figure 5 It is a schematic diagram showing the details of the cut groove from the side view of the first specimen;

[0052] Figure 6 It is a schematic diagram of the first straight specimen "wedged" into the thin blade along the groove to preform the mid-surface crack;

[0053] Figure 7 It is a schematic diagram of DCB loading where the first straight specimen is pulled apart along the mid-surface of the prefabricated crack;

[0054] Figure 8 It is a schematic diagram of the bending deformation of the two arms of the stretched DCB specimen;

[0055] Fig. 9 It is a schematic diagram of measuring the radius of curvature of a bending specimen;

[0056] Fig.10 It is a schematic diagram of the grinding surface of the third straight bar specimen with 90° ply to obtain 0° ply;

[0057] Among them, 1—SiC f / SiC composite plate; 2—1st straight strip specimen; 3—2nd straight strip specimen; 4—3rd straight strip specimen; 5—upper surface of plate; 6—lower surface of plate; 7—three layers of 90° ply on upper surface; 8—three layers of 90° ply on lower surface; 9—left end of 1st straight strip specimen; 10—side of 1st straight strip specimen; 11—groove cut at end; 12—groove root; 13—thin blade; 14—left clamp; 15—bolt; 16—base; 17—prefabricated crack; 18—right clamp; 19—upper loading block; 20—lower loading block; 21—upper arm; 22—lower arm; 23—90° ply side of upper arm; 24—90° ply side of lower arm; 25—upper contour line of lower arm. DETAILED DESCRIPTION

[0058] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0059] The features of various aspects of the embodiments of the present invention will be described in detail below. In the detailed description below, many specific details are proposed to fully understand the present invention. However, it is obvious to those skilled in the art that the present invention can also be implemented without these specific details. The following description of the embodiments is only for a better understanding of the present invention by illustrating examples of the present invention. The present invention is not limited to any specific settings and methods provided below, but covers all product structures, any improvements, replacements, etc. of methods covered without departing from the spirit of the present invention.

[0060] The following SiC laminate structure is prepared by a prepreg melt infiltration (MI) process. f The example of residual stress detection of SiC composite material is used to further illustrate the specific implementation of the present invention. The example is only used to explain and illustrate the present invention and does not constitute any limitation to the present invention. In the various drawings and the following description, well-known structures and technologies are not shown to avoid unnecessary ambiguity of the present invention.

[0061] Geometric description

[0062] The prepreg melt infiltration (MI) process was used to prepare SiC with a layer of [(90°)3 / (0°)6 / (90°)3] f / SiC composite material flat plate, the schematic diagram of the layering sequence of the flat plate is as follows Figure 2 The plate configuration and geometric dimensions are shown in Figure 3 As shown, the size of the plate should be large enough. The recommended size is length a = 120 mm, width b = 120 mm. The thickness is determined by the actual laying conditions. The nominal value of the single-layer thickness is 0.2 mm. The number of layers is 12, so the nominal thickness of the plate is 2.4 mm.

[0063] In the above SiC f Three slender straight strip specimens are cut from the middle of the SiC composite material plate, with the recommended dimensions of L = 100 mm long and W = 10 mm wide.

[0064] Material Description

[0065] (1) SiC f / SiC composite material prepreg is prepared by domestic second-generation SiC fiber with a fiber volume fraction of 20%.

[0066] (2) SiC f The nominal single-layer thickness of the / SiC composite prepreg after curing is 0.2 mm.

[0067] The steps of measuring the matrix residual stress of the SiCf / SiC composite material flat plate described in the embodiment by using a lamination process SiCf / SiC composite material matrix residual stress testing method proposed in the present invention are as follows:

[0068] Step 1: Prepare a SiCf / SiC composite material flat plate 1 with a ply ratio of [(90°)3 / (0°)6 / (90°)3] by using a prepreg-melt infiltration process. The ply sequence diagram of the flat plate is as follows: Figure 2 As shown, it includes three 90° plies 7 near the upper skin 5, and three 90° plies 8 near the lower skin 5, and the middle 6 plies are 0° plies. Then, three straight strip specimens are cut from the middle of the SiCf / SiC composite plate, as shown in FIG. Figure 3 As shown, they are the first straight bar sample 2, the second straight bar sample 3, and the second straight bar sample 4; the recommended dimensions of the three straight bar samples are: L = 100 mm long, W = 10 mm wide;

[0069] Step 2: Use water-guided laser to cut a groove 11 at one end 9 of the first straight strip sample 2 in the length direction and along the mid-surface in the thickness direction, such as Figure 4 The schematic diagram of observing the straight strip sample with the groove cut from the side 10 is as follows Figure 5 As shown, the height (i.e., width) t0 of the groove 11 is less than 0.5 mm, and the groove depth a0 is 10 mm;

[0070] Step 3: Place the first straight strip sample 2 vertically in a fixture that clamps the sample along the thickness direction. The schematic diagram of the fixture is as shown in Figure 6 As shown, it mainly includes four parts: base 16, left clamp 14, right clamp 18, and tightening bolt 15. When the straight strip specimen is clamped in the fixture, it is recommended that the clamping edge be h = 10mm away from the root of the groove, and the clamping force needs to be large enough to prevent the specimen from sliding. A thin blade 13 is "wedged" into the groove 11 of a straight strip specimen 2, so that the first straight strip specimen is further split at the middle surface, that is, a pre-crack 17 is generated at the root of the groove 11 in the middle surface of the specimen thickness direction. Adding the depth a0 of the previous groove, the final length of the introduced pre-crack is a p , thereby turning the straight strip specimen 2 into a double cantilever beam (DCB) specimen; the details of the above-mentioned operation of "wedging" a thin blade into the groove to preform a mid-surface crack can be further referred to ASTM C1940-24;

[0071] Step 4: Figure 7As shown in FIG. 1 , a loading block 19 is attached to the upper surface of the slotted side of the DCB specimen 2, and a loading block 20 is attached to the lower surface. The DCB specimen is pulled apart from the prefabricated crack 17 on the middle surface by using the loading method of the double cantilever beam test. The separated upper arm 21 and lower arm 22 of the DCB specimen are both asymmetric [(90°)3 / (0°)3] plies. Due to the release of residual stress, the upper arm 21 will bend toward the side of the surface where the 90° ply 23 is located, and the lower arm 22 will bend toward the side of the surface where the 90° ply 24 is located. Finally, both the upper and lower arms will become bent specimens, as shown in FIG. Figure 8 As shown;

[0072] Step 5: Take the lower arm 22 as an example to show the above mapping process. Figure 8 As shown, the imager is used to map the contour of the bent sample formed by the lower arm 22, and several points are taken in the middle part of the outer contour arc 25 to determine the curvature radius ρ of the bent sample, and then the thickness t and width W of the bent sample are measured with a vernier caliper. The upper arm 22 is mapped and dimensioned in the same way. Then the average value of the curvature radius ρ, thickness t and width W measured for the upper and lower arms is taken;

[0073] Step 6: Use a mechanical testing machine to load the second straight strip sample in the range of -70MPa to +70MPa, use an extensometer to measure the strain during loading, draw a stress-strain curve, and use the slope of the curve as the modulus E of the [(90°)3 / (0°)6 / (90°)3] ply sample. X The specimen can be further subjected to tensile loading to measure the complete tensile stress-strain curve of the [(90°)3 / (0°)6 / (90°)3] laminate specimen, and obtain data such as proportional limit, tensile strength, and fracture strain;

[0074] Step 7: Grind the upper and lower surfaces of the third straight strip sample, and remove the 90° layer close to the surface to obtain a straight strip sample with a layer of [0°]6, such as Fig.10 As shown, the two surfaces of the sample were then polished with 1 μm diamond paste to reduce the surface stress introduced by mechanical grinding;

[0075] Step 8: Use a mechanical testing machine to load the straight strip specimen of [0°]6 ply in the range of -70MPa to +70MPa, use an extensometer to measure the strain during the loading process, draw a stress-strain curve, and use the slope of the curve as the SiC f The modulus E0 of the SiC composite material in the 0° direction can be used to further tensile load the sample, measure the complete tensile stress-strain curve of the material in the 0° direction, and obtain data such as proportional limit, tensile strength, and fracture strain;

[0076] Step 9: According to the mixed law of modulus, the compression modulus E of the [(90°)3 / (0°)6 / (90°)3] laminated sample is measured. X 、SiC f / SiC composite material 0° direction modulus E0, calculate SiC f Modulus E of SiC composite material at 90° direction 90 Calculation of SiC based on the modulus mixing law f Modulus E of SiC composite material at 90° direction 90 The theoretical formula is shown in formula (1).

[0077] E 90= 2E X -E0(1)

[0078] Among them, E 90 For SiC f Modulus E of SiC composite material at 90° direction 90 ; E X The modulus of the straight specimen of the [(90°)3 / (0°)6 / (90°)3] ply.

[0079] Step 10: Using the matrix residual stress formula based on beam theory, the curvature radius ρ, specimen thickness t, specimen width W, modulus E0, modulus E 90 Substitute into the theoretical formula (2) to calculate the residual compressive stress σ of the matrix R .

[0080]

[0081] Among them, σ R For SiC f / SiC composite matrix residual compressive stress; E0 is SiC f The modulus E0 of the SiC composite material at 0° direction; I0 is the modulus of SiC with a ply ratio of [(90°)3 / (0°)3] f / SiC composite material bending specimen moment of inertia; ρ is the radius of curvature of the bending specimen; t is the thickness of the bending specimen.

[0082] Among them, the moment of inertia I0 is derived based on beam theory, and the function expression is shown in formula (3):

[0083]

[0084] Where W is the width of the bending specimen; α and β are intermediate variables, and the expressions are shown in formulas (4) to (5):

[0085]

[0086] The innovation of this invention lies in the SiC f Based on the characteristics of SiC composite materials, there are residual compressive stress in 0° plies and residual tensile stress in 90° plies. Therefore, when the straight strip specimen is cut from symmetrical plies to asymmetrical plies, bending deformation will occur under the action of residual stress. The specimen with a specific ply sequence is designed, so that the prepared symmetrical plies are cut from the middle and become asymmetrical plies. The bending moment balance is broken, and bending deformation occurs under the action of residual stress. A test scheme is designed, and the relationship between residual stress and bending curvature is established based on the beam theory of composite laminates to measure the residual stress.

[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the field can easily think of various equivalent modifications or substitutions within the technical scope disclosed by the present invention, and these modifications or substitutions should all be covered within the protection scope of the present invention.

Claims

1. A layering process SiC f A method for testing residual stress of a SiC composite material matrix, characterized in that: The method comprises the following steps: Step 1: Prepare a SiCf / SiC composite material plate with a layer of [(90°)3 / (0°)6 / (90°)3] by using a prepreg-melt infiltration process, and then f At least 3 straight specimens are cut from the middle of the / SiC composite material plate; Step 2: Cut a groove at one end of the first straight strip sample at the mid-surface along the thickness direction. The height of the groove is no more than 1 / 10 of the thickness of the sample, and the depth of the groove is 5 to 10 times the thickness of the sample. Step 3: vertically place the first straight strip sample in a fixture that clamps the sample in the thickness direction, "wedge" a thin blade in the groove, introduce a pre-crack in the middle surface of the first straight strip sample in the thickness direction, and obtain a double cantilever beam sample; Step 4: Paste loading blocks on the upper and lower surfaces of the slotted side of the DCB specimen, and use the loading method of the double cantilever beam test to pull the DCB specimen apart from the prefabricated crack on the middle surface. The upper and lower arms of the separated DCB specimen are both asymmetric [(90°)3 / (0°)3] plies. Due to the release of residual stress, the upper and lower arms will bend toward the surface where the 90° ply is located, turning into a bent specimen. Step 5: Measure the contours of the two bending specimens, and select several points in the middle of the outer contour arc to determine the curvature radius ρ of the bending specimens, then measure the thickness t and width W of the bending specimens and take the average value; Step 6: Load the second straight strip sample in the range of -70MPa to +70MPa, measure the strain during loading, draw a stress-strain curve, and use the slope of the curve as the modulus E of the [(90°)3 / (0°)6 / (90°)3] ply sample. X ; Step 7: Grind the upper and lower surfaces of the third straight strip sample, cut off the 90° ply close to the epidermis, obtain a straight strip sample with a ply of [0°]6, and then polish the two surfaces of the sample with diamond paste; Step 8: Load the straight strip specimen of [0°]6 ply in the range of -70MPa to +70MPa, measure the strain during loading, draw the stress-strain curve, and use the slope of the curve as the SiC f / The modulus E0 of SiC composite material at 0° direction; Step 9: Use the measured compression modulus E of the [(90°)3 / (0°)6 / (90°)3] ply sample X 、SiC f / SiC composite material 0° direction tensile modulus E0, reverse calculation of SiC f Modulus E of SiC composite material at 90° direction 90 ; Step 10: The curvature radius ρ, sample thickness t, sample width W, modulus E0, modulus E 90 Substitute into the theoretical formula (1) to calculate the residual compressive stress σ of the matrix R ; Among them, σ R For SiC f / SiC composite matrix residual compressive stress; E0 is SiC f The modulus E0 of the SiC composite material at 0° direction; I0 is the modulus of SiC with a ply ratio of [(90°)3 / (0°)3] f / SiC composite material bending specimen moment of inertia; ρ is the curvature radius of the bending specimen; t is the thickness of the bending specimen; Among them, the expression of the moment of inertia I0 is shown in formula (2): Where W is the width of the bending specimen; α and β are intermediate variables, and the expressions are shown in formula (3) to formula (4):

2. The testing method according to claim 1, characterized in that: SiC prepared in step 1 f The size of the SiC composite plate is 120 mm long × 120 mm wide; f The three straight specimens cut from the middle of the SiC composite material flat plate are in the shape of thin strips with dimensions of 100 mm long × 10 mm wide.

3. The testing method according to claim 1, characterized in that: Step 3: The operation of "wedging" a thin blade into the groove to preform a mid-surface crack is based on ASTM C1940-24.

4. The testing method according to claim 1, characterized in that: Step 9 Calculate SiC based on the modulus mixing law f Modulus E of SiC composite material at 90° direction 90 The theoretical formula of is shown in formula (5), BY 90 =2E X -E0(5) Among them, E 90 For SiC f Modulus E of SiC composite material at 90° direction 90 ; E X The modulus of the straight specimen of the [(90°)3 / (0°)6 / (90°)3] ply.

5. The testing method according to claim 1, characterized in that: The method is applicable to SiC laminated structures prepared by prepreg melt infiltration process. f / SiC composite materials.

6. The testing method according to claim 1, characterized in that: Lamination process SiC f / SiC composite materials are prepared using unidirectional prepreg.

7. The testing method according to claim 1, characterized in that: The height of the groove in step 2 is no more than 0.5 mm, and the depth of the groove is 10 mm.

8. The testing method according to claim 1, characterized in that: The groove described in step 2 is cut by water-conducting laser.

9. The testing method according to claim 1, characterized in that: In step five, an imager is used to map the contours of the two bending specimens; and a vernier caliper is used to measure the thickness and width of the bending specimens.

10. The testing method according to claim 1, characterized in that: When used for comparative testing, the number of specimens cut in step 1 shall be a multiple of 3.

Citation Information

Cited By

  • Method for measuring residual stress of bent box type steel member and establishing model

    CN122217526A